Pengaruh Desain, Promosi Dan Brand Image Terhadap Keputusan Pembelian Konsumen Produk Air Mineral Pada Mahasiswa Universitas Muhammadiyah Surakarta - Gana, Ardha Brawidha, Basworo Dibyo, S.E, M.Si (2017)
The research aims to identify and empirically examine (1) the influence of design on product purchasing decisions mineral water. (2) the effect of promotions on product purchasing decisions mineral water. (3) the effect of brand image on product purchasing decisions mineral water. (4) the effect of design, promotion and brand image simultaneously on product purchasing decisions mineral water. This research is quantitative. Samples from this study are students of Muhammadiyah University of Surakarta by 100 respondents by random sampling sampling techniques. Methods of data collection using questionnaires. Data analysis techniques is multiple regression analysis, t-test, F test, and the coefficient of determination (R2). The results showed there is influence between the independent variable on the dependent variable. F test analysis known to have a simultaneous effect of design variables, promotion, and brand image on product purchasing decisions mineral water.